Metastatic Cancer of Apparent Colon Origin With No Intraluminal Cancer After Resection of Colorectal Lateral Spreading Lesions. Issue 1 (28th January 2022) - Lee, Christopher J.; Vemulapalli, Krishna C.; Lin, Jingmei; Rex, Douglas K.
ABSTRACT: We report a case of metastatic adenocarcinoma to the liver that presented 5 months after piecemeal endoscopic mucosal resection of 3 benign lateral spreading adenomas in the cecum. The pathologic features of the metastatic cancer indicated a probable colonic origin. However, when the cancer was identified, there was no endoscopic evidence of recurrent polyp or another primary lesion in the colon.